Towards global indicator of durability performance and carbon footprint of clinker-slag-limestone cement-based concrete exposed to carbonation. (20th December 2022) - Elkhaldi, Imane; Roziere, Emmanuel; Turcry, Philippe; Loukili, Ahmed
Abstract: This article aims at defining an effective global warming potential criterion for qualifying a concrete mixture based on a CO2 calculation and durability performance tests, as well as understanding the parameters that influence the duration of initiation and propagation of corrosion in concretes exposed to carbonation-induced corrosion. An experimental study was conducted in order to assess the resistance to carbonation and the electrical resistivity for concretes made of multi-composite cements with ground-granulated blast furnace slag (GGBS) and limestone in the limits of new cement European standard EN 197-5, and to understand the link between these properties and the composition of the cements. A model is presented which allows to predict the service life of the concrete cover from the material data of the concrete (accelerated carbonation rate, electrical resistivity), environmental parameters (HR, T, CO2 ) and minimum cover. It was found that the reactive CaO content of cements influences the carbonation rate of concrete, and the electrical resistivity and the GGBS content of cements were found to have a good correlation. The model used allows comparing the studied cements from the CO2 emission/service life ratios.